Penguatan Keterampilan Abad Ke-21 dan Pengembangan Efikasi Diri Mahasiswa Pendidikan Akuntansi - Ramdhany, Muhamad Arief; Setiawan, Yana; Hardiana, R. Dian; Sobandi, A. (Universitas Pendidikan Indonesia, 2020)
This purpose of this study is to analyze the effect of strengthening 21st Century Skills (Learning Skills, Literacy Skills, and Life Skills) on development of Self-Efficacy of the Accounting Education Students at Faculty of Eco-nomics and Business Education, Universitas Pendidikan Indonesia. To collect data, the questionnaire was used. Out of 256 population of students, 154 were selected as representative sample. The Partial Least Square Struc-tural Path-Modeling (PLS-PM) was used to test the hypotheses. The research outcomes revealed that the Learn-ing Skills, Literacy Skills, and Life Skills have positive effect on Self-Efficacy. The implication of this study is that the students self-efficacy will develop more with the strengthening 21st Century Skills.